Synthesis and Antibacterial Activities of Sugar-containing Platinum Ethynyl Complexes - Paul, Ratan Kumar; Ahmad, Md Faruak; Khan, Mohammad Mizanur Rahman; Younus, Muhammad (Journal of Bangladesh Academy of Sciences, 2016)
New sugar-containing aryl ethynyl ligand [N-(4-trimethylsilylethynylphenyl)-?-D-glucopyranosylamine] 2 has been prepared by the reaction of [N-(4-iodophenyl)-?-D-glucopyranosylamine] 1 with trimethysilylacetylene in the presence of Pd(OAc)2/CuI catalyst, in iPr2NH and DMF solvent mixture. The trimethylsilyl group of compound 2 was deprotected using K2CO3 in methanol to form terminal ethynylene ligand [N-(?-D-glucopyranosyl)aniline-4-ethyne] 3. Novel platinum mono-ethynyl complex trans-[(P(Bu)3)2PtCl(C?C-4-C6H4-NH-D-glocose)] 4 and bis-ethynyl complex trans-[(P(Bu)3)2PtCl(C?C-4-C6H4-NH-D-glocose)2] 5 were formed by the dehydrohalogenation reaction of trans-[Pt(P(Bu)3)2Cl2] with terminal ethynyl ligand 3 in iPr2NH/THF, in the presence of CuI, at 65ºC. The complexes are hygroscopic in air, and are fairly soluble in methanol and CH2Cl2. The new compound 2 - 5 were characterized by FTIR and UV-Vis spectroscopy and elemental analysis. The compounds were tested for antibacterial activity using disk diffusion technique. The platinum complexes 4 and 5 displayed good resistivity against the following bacteria: Escherichia coli, Proteus penneri, Klebsiella oxytoca and Pseudomonas aeruginosa. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 65-77, 2016 <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> New sugar-containing aryl ethynyl ligand [N-(4-trimethylsilylethynylphenyl)-?-D-glucopyranosylamine] 2 has been prepared by the reaction of [N-(4-iodophenyl)-?-D-glucopyranosylamine] 1 with trimethysilylacetylene in the presence of Pd(OAc)2/CuI catalyst, in iPr2NH and DMF solvent mixture. The trimethylsilyl group of compound 2 was deprotected using K2CO3in methanol to form terminal ethynylene ligand [N-(?-D-glucopyranosyl)aniline-4-ethyne] 3. Novel platinum mono-ethynyl complex trans-[(P(Bu)3)2PtCl(C?C-4-C6H4-NH-D-glocose)] 4 and bis-ethynyl complex trans-[(P(Bu)3)2PtCl(C?C-4-C6H4-NH-D-glocose)2] 5 were formed by the dehydrohalogenation reaction of trans-[Pt(P(Bu)3)2Cl2] with terminal ethynyl ligand 3 in iPr2NH/THF, in the presence of CuI, at 65ºC. The complexes are hygroscopic in air, and are fairly soluble in methanol and CH2Cl2. The new compound 2 - 5 were characterized by FTIR and UV-Vis spectroscopy and elemental analysis. The compounds were tested for antibacterial activity using disk diffusion technique. The platinum complexes 4 and 5 displayed good resistivity against the following bacteria: Escherichia coli, Proteus penneri, Klebsiella oxytoca and Pseudomonas aeruginosa. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 65-77, 2016 <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->